Membrane Active Antimicrobial Peptides: Translating Mechanistic Insights to Design - Li, Jianguo; Koh, Jun-Jie; Liu, Shouping; Lakshminarayanan, Rajamani; Verma, Chandra S.; Beuerman, Roger W. (Frontiers in Neuroscience, 2017)
Antimicrobial peptides (AMPs) are promising next generation antibiotics that hold great potential for combating bacterial resistance. AMPs can be both bacteriostatic and bactericidal, induce rapid killing and display a lower propensity to develop resistance than do conventional antibiotics. Despite significant progress in the past 30 years, no peptide antibiotic has reached the clinic yet. Poor understanding of the action mechanisms and lack of rational design principles have been the two major obstacles that have slowed progress. Technological developments are now enabling multidisciplinary approaches including molecular dynamics simulations combined with biophysics and microbiology toward providing valuable insights into the interactions of AMPs with membranes at atomic level. This has led to increasingly robust models of the mechanisms of action of AMPs and has begun to contribute meaningfully toward the discovery of new AMPs. This review discusses the detailed action mechanisms that have been put forward, with detailed atomistic insights into how the AMPs interact with bacterial membranes. The review further discusses how this knowledge is exploited towards developing design principles for novel AMPs. Finally, the current status, associated challenges and future directions for the development of AMP therapeutics are discussed.